Equilibrium and kinetic studies of the adsorption of antibiotics from aqueous solutions onto powdered zeolites - de Sousa, Diana Nara Ribeiro; Insa, Sara; Mozeto, Antonio Aparecido; Petrovic, Mira; Chaves, Thiago Faheina [UNESP]; Fadini, Pedro Sergio (Elsevier, 2018)
The performances of two FAU-type zeolites with different SiO2/Al2O3 ratios were evaluated for the removal of antibiotics of three different classes, namely azithromycin, ofloxacin, and sulfamethoxazole, from aqueous solutions. Commercial zeolites were used, without any previous treatment. Use of a small adsorbent dosage resulted in fast antibiotic adsorption that followed pseudo-second order kinetics. The removals of azithromycin and sulfamethoxazole were highly pH-dependent, with low removal percentages observed under acid (pH 2.5–4.5) and basic (pH 8.5–10.5) conditions, respectively. The Freundlich isotherm model provided the best fits to the adsorption data. The adsorption mechanisms appeared to involve both electrostatic and H-bonding interactions. Using an antibiotics mixture, percentage removals of azithromycin and ofloxacin onto the zeolites of up to 79% were obtained. Both materials presented good adsorption (>50%) of azithromycin and ofloxacin from a real sample of effluent wastewater. The results showed that zeolites with FAU structure can be used as effective adsorbents for the removal of antibiotics with different physicochemical properties, including molecules with large volumes, such as azithromycin.
Keywords: Antibiotics; Effective removal; Fast adsorption; Zeolite